Reconstruction of the Business Judgment Rule Doctrine in Indonesia: Legal Comparison with England, Canada, the United States, and Australia - Santiago, Faisal (Magister of Law, Faculty of Law, University of Mataram, 2024)
This research specifically analyzes the comparison of the substance of the business judgment rule doctrine in Indonesia with that in other countries by comparing several countries, namely: England, Canada, the United States and Australia. The aim of this research is to reconstruct the future regulation of the business judgment rule doctrine in Indonesia. This research is normative legal research that prioritizes conceptual, statutory, case, and comparative approaches. The research results show that the principles related to the business judgment rule doctrine in Indonesia include the principle of good faith, the principle of prudence, the principle of expediency, and the principle of legal certainty. The characteristics of the business judgment rule doctrine in Indonesia, as contained in statutory regulations and court decisions, actually emphasize the mechanisms that must be taken by directors before making a decision, namely the obligation to prioritize the willens aspect, namely knowing a decision to be taken, and the wettens aspect, namely wanting and understanding the potential consequences. by a decision to be taken. Reconstructing the business judgment rule doctrine in Indonesia by referring to practices in England, Canada, the United States, and Australia, the BJR regulations in Indonesia actually require reconstruction or updating in the future by formulating specific regulations regarding the BJR doctrine in Indonesia and providing space for judicial institutions to develop the application of the BJR doctrine according to developing cases.